2010
DOI: 10.2353/ajpath.2010.100328
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor MIST1 Is a Novel Human Gastric Chief Cell Marker Whose Expression Is Lost in Metaplasia, Dysplasia, and Carcinoma

Abstract: The lack of reliable molecular markers for normal differentiated epithelial cells limits understanding of human gastric carcinogenesis. Recognized precursor lesions for gastric adenocarcinoma are intestinal metaplasia and spasmolytic polypeptide expressing metaplasia (SPEM), defined here by ectopic CDX2 and TFF2 expression, respectively. In mice, expression of the bHLH transcription factor MIST1, normally restricted to mature chief cells, is down-regulated as chief cells undergo experimentally induced metaplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(159 citation statements)
references
References 98 publications
(113 reference statements)
6
148
2
Order By: Relevance
“…This suggests that the UPR may have a mechanistic role in the transdifferentiation of mature chief cells into metaplasia as reported previously. 8,21 Lack of ER stress response during acute Helicobacter infection suggests activation of the UPR may be a reparative response of gastric epithelium to chronic Helicobacter infection. We hypothesize that in the Helicobacter-infected gastric mucosa, prolonged ER stress following chronic inflammation, compounded by aberrant mucin synthesis in the metaplastic cells triggers UPR activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the UPR may have a mechanistic role in the transdifferentiation of mature chief cells into metaplasia as reported previously. 8,21 Lack of ER stress response during acute Helicobacter infection suggests activation of the UPR may be a reparative response of gastric epithelium to chronic Helicobacter infection. We hypothesize that in the Helicobacter-infected gastric mucosa, prolonged ER stress following chronic inflammation, compounded by aberrant mucin synthesis in the metaplastic cells triggers UPR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of HSPA5 was also seen in the inflammatory infiltrates in these patients although no abnormality in HSPA5 expression in chronic gastritis was observed, as also seen by qPCR ( Figure 1c). As recent studies have shown that transdifferentiation of chief cells contributes to gastric metaplasia in the human 21 and mouse, 8 we specifically examined HSPA5 expression in chief cells using MIST1 as a chief cell marker. In the normal human gastric mucosa, HSPA5 was expressed at a low level in the chief cell compartment at the bases of glands, correlating with MIST1 expression (Figure 2e).…”
Section: Im In Human Is Associated With Increased Hspa5 Protein Exprementioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed automatically using a Benchmark XT automated slides stainer (Ventana Medical Systems, Inc., Tucson, AZ) using established protocols. 24 In brief, protocols consisted of pretreatment with CC1 (pH 8.0), incubation with primary antibodies, and detection using an IVIEW-DAB (diaminobenzidine) detection system (catalog No. 760-500; Ventana Medical Systems, Inc.) including ultraview inhibitor, horseradish peroxidase, multimer, chromogen, H 2 O 2 , and copper.…”
Section: Immunolabelingmentioning
confidence: 99%
“…760-501; Ventana Medical Systems, Inc.) including enhancer, naphthol, red A, and fast red B. Immunofluorescence was performed manually according to established protocols. 24,25 In brief, sections were washed for 5 minutes (xylene ϫ3, 100% ethanol ϫ2, 95% ethanol ϫ1, 70% ethanol ϫ1, and PBS ϫ1), boiled in Trilogy for antigen retrieval (Cell Marque, Hot Springs, AR), rinsed in deionized water for 15 minutes, and washed with PBS. Sections were blocked in 1% bovine serum albumin and 0.3% Triton X-100 in PBS and were incubated using combinations of the primary antibodies.…”
Section: Immunolabelingmentioning
confidence: 99%
See 1 more Smart Citation